Widespread potential for streamflow leakage across Brazil - José Gescilam S. M. Uchôa; Paulo Tarso S. Oliveira; André S. Ballarin; Antônio A. Meira Neto; Didier Gastmans; Scott Jasechko; Ying Fan; Edson C. Wendland (Nature Communications)
Abstract River-aquifer interactions play a crucial role in water availability, influencing environmental flows and impacting climate dynamics. Where groundwater tables lie below river water levels, stream water can infiltrate into the underlying aquifer, reducing streamflow. However, the prevalence of these “losing” rivers remains poorly understood due to limited national-wide in situ observations. Here we analyze water levels in 17,972 wells across Brazil to show that most of them (55%) lie below nearby stream surfaces, implying that these nearby streams are likely seeping into the subsurface. Our results demonstrate the widespread potential for stream water losses into underlying aquifers in many regions of the country, especially in areas with extensive groundwater pumping. Our direct observations underscore the importance of conjunctively managing groundwater and surface water, and highlight the widespread risk of streamflow losses to aquifers, which could impact global water access and ecosystems that rely on rivers.